A Short Intervention and an Interactive e-Learning Module to Motivate Medical and Dental Students to Enlist as First Responders: Implementation Study - Victor Taramarcaz; Tara Herren; Eric Golay; Simon Regard; Sébastien Martin-Achard; Francois Mach; Nicolas Schnetzler; Gaëtan Ricci; Ido Zamberg; Robert Larribau; Marc Niquille; Mélanie Suppan; et al. (JMIR Publications, 2022)
BackgroundPrompt and proficient basic life support (BLS) maneuvers are essential to increasing the odds of survival after out-of-hospital cardiac arrest. However, significant time can elapse before the arrival of professional rescuers. To decrease these delays, many countries have developed first responder networks. These networks are composed of BLS-certified lay or professional rescuers who can be dispatched by emergency medical communication centers to take care of those who experience out-of-hospital cardiac arrest. Many systems are, however, limited by a relatively low number of active first responders, and first-year medical and dental students may represent an almost untapped pool of potential rescuers. On top of providing an enhanced BLS coverage to the population, this could also help medical students be better prepared to their future role as certified health care providers and address societal expectations regarding health care students. ObjectiveOur objective was to describe the impact of a short motivational intervention followed by a blended BLS course (e-learning and practice session) designed to motivate first-year medical and dental students to enlist as first responders. MethodsA short, web-based, motivational intervention presenting this project took place, and first-year University of Geneva, Faculty of Medicine students were provided with a link to the study platform. Those who agreed to participate were redirected to a demographic questionnaire before registering on the platform. The participants were then asked to answer a second questionnaire designed to determine their baseline knowledge prior to following an interactive e-learning module. Upon completion, a web-based booking form enabling them to register for a 1-hour practice session was displayed. These sessions were held by senior medical students who had been trained and certified as BLS instructors. The participants who attended these practice sessions were asked to answer a postcourse questionnaire before receiving the certificate enabling them to register as first responders. ResultsOut of the 529 first-year students registered at University of Geneva, Faculty of Medicine on January 14, 2021, 190 (35.9%) initially agreed to participate. Moreover, 102 (19.3%) attended the practice sessions, and 48 (9.1%) had completed all training and enlisted as first responders on the dedicated platform, Save a Life, at 6 months (July 14, 2021). Postcourse confidence in resuscitation skills was associated with a higher likelihood of registering as first responder (P=.03). No association was found between prior BLS knowledge and the probability of registering to a practice session (P=.59), of obtaining a course completion certificate (P=.29), or of enlisting as first responder (P=.56). ConclusionsThis study shows that a motivational intervention associated with a short BLS course can convince medical students to enlist as first responders. Further studies are needed to understand the rather low proportion of medical students finally registering as first responders. International Registered Report Identifier (IRRID)RR2-10.2196/24664